Designing for "challenge" in a large‐scale adaptive literacy game for primary school children. (6th July 2021) - Benton, Laura; Mavrikis, Manolis; Vasalou, Asimina; Joye, Nelly; Sumner, Emma; Herbert, Elisabeth; Revesz, Andrea; Symvonis, Antonios; Raftopoulou, Chrysanthi
Abstract: The use of learning games within the classroom is becoming increasingly common because of their potential to positively impact learning. Recent developments in adaptivity offer further possibilities to personalise learning by tailoring the game to an individual child's level or particular learning needs. However, designing an adaptive learning game is a complex process as many different game components have an impact on the provision of optimal challenge, crucial for maintaining player engagement, with limited prior work considering the multifaceted nature of this concept. This paper explores how to design for "challenge" within large‐scale adaptive learning games through a case study focused on the design of a literacy game for three linguistically and cognitively diverse learner groups—novice readers, children with dyslexia and children learning English as a foreign language. In reflecting on our design process, we identify three key design tensions that arose: (a) supporting longer‐term learning goals through game replayability; (b) fostering either replication or innovation in pedagogy through adaptivity rules; and (c) addressing diversity between learner groups. We present a set of design recommendations to guide researchers and designers in taking a multidimensional view of challenge when designing large‐scale adaptive learning games. Practitioner notes What is already known about this topic? Adaptive learning games can have a positive impact on children's learning outcomes. Ensuring optimal challenge within games is important for maintaining engagement. Designing adaptive learning games is a complex process. What this paper adds? Designing for optimal challenge within adaptive learning game should be considered as a multifaceted concept. Identification of key tensions related to optimising challenge that can emerge during the design of large‐scale adaptive learning games. Recommendations for adaptivity researchers and learning game designers for how to address these tensions in adaptive learning game design. Implications for practice and/or policy? We need a more systematic approach to adaptivity game design to ensure wider spread adoption. Learning game designers seeking to utilise adaptive components in designing for optimal challenge should consider a focus on learners who may require a more targeted approach. Adaptive learning games offer opportunities for pedagogical innovation in the classroom through exploiting innovative game features as well as large‐scale data collection to support adaptive learning over time.